West East: Imagining the Line - Kapustin, Petr (project baikal, 2017)
The article observes several historical, present-day and possible forms of the idea of the geographical west-east line.  It is stated that formation of the future depends on the chosen way of objective imagination. The long-term vision of the future connection between West and East is proposed.
Keywords: West; East; regions; geoline; forms of the idea of the line; metaphors and images in development management.